P219 Evaluation of the utility of the breathing pattern assessment tool in a post-covid syndrome MDT assessment clinic. (11th November 2022) - Grillo, L; Turnbull, J; Lee, JS; Froome, L; Maxwell, J; Webber, L; Weatherly, L; Curtis, A; Osman, L
Abstract : Introduction: Breathing pattern dysfunction (BPD) describes when an individuals breathing is disconnected from their respiratory or metabolic requirements. BPD is a recognised reason for sustained breathlessness and is acknowledged as important in post-COVID syndrome 1 (PCS). The Breathing Pattern Assessment Tool (BPAT) is used to assess and screen for BPD. A score of ≥4 being a trigger for potential onward referral to a specialist physiotherapist for assessment 2 . Objectives: Evaluate the utility of the BPAT in a PCS assessment clinic Compare BPAT scores with other outcome measures of breathlessness, BPD and QoL. Methods: A convenience sample of consecutive patients attending PCS assessment clinic between October 2021 and May 2022 was used. Patients had sustained symptoms 12-weeks following initial COVID-19 infection, not explained by an alternative diagnosis. Patients completed BPAT, Nijmegen Questionnaire (NQ), EQ5D, PHQ, GAD7 and symptom-based numerical rating scales (NRS). The BPAT was carried out by the specialist physiotherapists and occupational therapists. Results are described as mean (standard deviation) and frequencies. Correlations between measures were completed using Pearson's correlation coefficient. Results: Seventy-three patients were included ( table 1 ). Twenty-eight (38%) had a BPAT>4, 15(54%) of which were referred on to a specialist respiratory physiotherapy service for specific BPD treatment. The BPAT showed moderate correlation with the NQ (r=0.303, p>0.001) and weak correlations with NRS for breathlessness (r=0.305, p>0.014), cough (r=0.265, p>0.034) and fatigue (r=0.254, p>0.043). The NQ correlated moderately with both the PHQ (r= 0.578, p>0.001) and GAD7 (r=0.485, p>0.001). Conclusion: The BPAT Tool is a useful component of breathlessness assessment in the context of a PCS assessment clinic. It can provide a useful screening tool to identify patients with BPD who may benefit from specialist intervention with respiratory physiotherapists. Further understanding is required of how BPD responds to therapy and which type of treatments are important for this cohort. References: Hylton H, Long A, Francis C, et al . Real-world use of the Breathing Pattern Assessment Tool in assessment of breathlessness post-COVID-19. Clin Med (Lond) . 2022 Jun 27. Todd S, Walsted ES, Grillo L et al . Novel assessment tool to detect BPD in patients with refractory asthma. Respirology . 2018;23 (3).